2023
DOI: 10.1136/bmjophth-2023-001283
|View full text |Cite
|
Sign up to set email alerts
|

Refractive error, eye care needs and attitude towards spectacle wearing among older Zanzibari craftswomen and implications for developing women-targeted services: a cross-sectional study

Ving Fai Chan,
Fatma Omar,
Adrianna Farmer
et al.

Abstract: BackgroundAged Zanzibari women are in a disadvantaged position, having high demand for near-vision spectacles. Currently, there is no information on the eye health status of craftswomen, which makes planning a women-targeted project to deliver eye health services to older craftswomen in Zanzibar difficult. We assessed the prevalence of vision impairment, refractive error, presbyopia, effective spectacle coverage (distance and near) and attitude towards spectacle wearing among older Zanzibari craftswomen.Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…A survey was then carried out to assess the eye health needs and attitudes towards eye health among elderly craftswomen. 27 The survey revealed a significant prevalence of uncorrected presbyopia (86.6%), accompanied by remarkably low spectacle coverage (0.99%). 27 These findings establish a baseline for assessing the impact of spectacle correction.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…A survey was then carried out to assess the eye health needs and attitudes towards eye health among elderly craftswomen. 27 The survey revealed a significant prevalence of uncorrected presbyopia (86.6%), accompanied by remarkably low spectacle coverage (0.99%). 27 These findings establish a baseline for assessing the impact of spectacle correction.…”
Section: Discussionmentioning
confidence: 98%
“… 27 The survey revealed a significant prevalence of uncorrected presbyopia (86.6%), accompanied by remarkably low spectacle coverage (0.99%). 27 These findings establish a baseline for assessing the impact of spectacle correction. Additionally, the same study indicated a positive attitude among craftswomen towards wearing spectacles.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations